Penyuluhan Gizi Seimbang Dan Pemberian Makanan Tambahan Bagi Anak Balita Dalam Rangka Mencegah Stunting Di Dusun I Desa Oelomin Kecamatan Nekamese Kabupaten Kupang - esem, odilia; Mindarsih, Theresia; Ernestin, Meri Flora (Jurnal Pengabdian kepada Masyarakat Nusantara, 2024)
Nutrition is an important part of health and development. Good nutrition is linked to improved health of babies, children and mothers, as well as a stronger immune system. About 45% of deaths in children under 5 years of age are caused by malnutrition. This occurs mostly in low and middle income countries. The aim of implementing this community service activity is to increase mothers' knowledge in preventing stunting in toddlers. The method used in this service is providing education using lecture and question and answer methods as well as providing additional food to toddlers who are present during the activity. There was a clear difference in participants' knowledge before and after being given the material. The majority of participants were able to answer questions correctly and precisely after being given the material, namely 76%. After carrying out this community service activity, mothers who have toddlers can increase their knowledge of toddler nutrition problems. Educational activities help mothers who have toddlers understand nutritional problems in toddlers. This can be seen by increasing mothers' knowledge of providing balanced nutrition for toddlers.